CANGKANG PALA SEBAGAI MATERIAL PENGGANTI SEBAGIAN AGREGAT KASAR PADA BETON NORMAL - Budiman Budiman; Imran Imran; James WTP (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract Normal concrete uses fine aggregate and coarse aggregate with concrete density 2200 kg/m3 -2400 kg/m3 with a compressive strength of about 15-40 MPa. The purpose of this study is to determine characteristics of the concrete aggregate and the compressive strength of the concrete design based on the DOE (Department of Environment) method and the SNI Standard. In this research, the use of nugmet shell was varied as follows: 0%, 0,25%, 0,50%, 0,75% and 1% of the cement weight. The results showed that the use of nutmeg shells as a normal concrete affected the specific gravity and the value compressive strength of concrete. The higher the percentage of nutmeg shells, the lower the specific gravity and compressive strength of the concrete. The average value of concrete density to nutmeg shell 2254.72 (kg/m3 ) and normal concrete 2304.32 (kg/m3 ). The compressive strength of normal concrete is 224.2 kg/cm2 and the concrete from nutmeg shell the composition of 0.25% and 0.5% obtained by 129.6 kg/cm2 and 140.0 kg/cm2 increases the use of nutmeg shell 0.75% and 1% obtained value of 117.6 kg/cm2 and 118.1 kg/cm2 decreased at the age of 28 days. The compressive strength of normal concrete 22 MPa while the maximum nutmeg shell concrete 14 MPa, so it does not meet the quality of normal concrete in general. Keywords: Aggregate Characteristics, nutmeg shell, Characteristics Compressive Strength